Identifying feeding plants for trigona sp. species in royal honey sakah, gianyar regency, bali - Ni Ketut Ayu Juliasih; I Nyoman Arsana; Ni Nyoman Sri Puspa Adi (Institute of Computer Science (IOCS), 2022)
Plants are one of the sources of feed for honey bees to carry out their lives. Currently, the identification of honey-producing plants still needs to be carried out. This research examines the types of plant species used as a source of food for Trigona sp. bees at Royal Honey Sakah in Gianyar, Bali. Qualitative descriptive research uses observation, documentation, and direct interviews with agro-tourism owners. Royal Honey Sakah's investigation will continue until May 2022. As a result, Royal Honey Sakah provides several types of plants as a feed source for Trigona spp. bees. Red Santos (Xanthostemon novoguineensis), which has the largest population, is followed by santos lemon (Xanthostemon chrysanthus), Bidarasari (Porana volubilis), red Kaliandra (Calliandra calothyrsus), bridal tears (Antigonon leptopus), Batavia (Jatropha intergerrima), and princess's palm (Veitchia merillii). The plant produces nectar that is much needed by bees. The number of honey bees depends heavily on the availability of nectar from plants.